2021
DOI: 10.3390/nu13103428
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Dietary Intake over a 20-Year Period in People with Type 2 Diabetes in Japan: A Comparative Study of Two Nationwide Registries; Japan Diabetes Complications Study (JDCS) and Japan Diabetes Clinical Data Management Study (JDDM)

Abstract: Background: In order to provide effective dietary guidance, it is necessary to consider dietary intake, which can change over time. This study analyzed changes in the diet of Japanese patients with type 2 diabetes over a 20-year period. Methods: We compared the results of two dietary surveys that used the food frequency questionnaire format. The first was conducted in 1996 by the Japan Diabetes Complications Study (JDCS) (n = 1509; males 53.3%), and the second in 2014–2018 by the Japan Diabetes Clinical Data M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although we observed a marked increase in total fat intake in Japan, mostly due to increased plant fat intake, the prevalence of T2DM and the national average HbA1c continue to increase. A recent analysis of two Japanese nationwide diabetes registries noted an increase in fat and meat intake with significant decreases in the intake of fish, soy products, fruits, and vegetables among people with diabetes over a 20-year period [25]. Although Japan is recognized for its seafood diet, our findings concurringly showed that the Japanese population consumed less seafood and more meat in the past two decades.…”
Section: Discussionsupporting
confidence: 82%
“…Although we observed a marked increase in total fat intake in Japan, mostly due to increased plant fat intake, the prevalence of T2DM and the national average HbA1c continue to increase. A recent analysis of two Japanese nationwide diabetes registries noted an increase in fat and meat intake with significant decreases in the intake of fish, soy products, fruits, and vegetables among people with diabetes over a 20-year period [25]. Although Japan is recognized for its seafood diet, our findings concurringly showed that the Japanese population consumed less seafood and more meat in the past two decades.…”
Section: Discussionsupporting
confidence: 82%
“…One basis for formulating an intake recommendation is to mimic the intake of regions that have traditionally consumed soyfoods, especially China and Japan, given their long history of consumption. Interestingly, national surveys in China indicate soy intake increased over a recent 40-year period ( 568 ) whereas in Japan, data indicate soy intake decreased, especially in relation to total protein intake ( 45 , 569 ). Despite the increase in China, He et al ( 568 ) reported that <30% of the Chinese population meets the ≥10 g soybeans/1,000 kcal recommendation.…”
Section: Intake Recommendationsmentioning
confidence: 99%